Wind tunnel testing of telecommunication lattice towers equipped with ancillaries. (15th August 2021) - Calotescu, Ileana; Torre, Stefano; Freda, Andrea; Solari, Giovanni
Highlights: Telecommunication lattice towers are investigated. Wind tunnel tests are performed on sectional models equipped with ancillaries. The presence of ancillaries results in an increase of both drag and lift coefficients. Drag coefficients resulted much larger than lift coefficients. Abstract: Lattice towers are used in several fields such as radio and television broadcasting, wireless communication or mobile networking. These are lightweight structures which are used to support specific equipment to certain heights such as for examples antennas needed for signal transmission. The purpose of this paper is to investigate the influence of ancillary elements on the aerodynamic coefficients of telecommunication lattice towers. To this aim, three wind tunnel tests have been conducted on the sectional model of a real telecommunication tower located in Romania. The leg members have circular cross-sections whereas the diagonal and horizontal members have angle cross-sections. In order to investigate the effect of the cross-section of elements on the aerodynamic coefficients, an additional model having circular cross-sections for the diagonal and horizontal members was considered. The first wind tunnel test was conducted on the bare models, in the second test the models were equipped with a ladder and feeder cables whereas for the third test both the ladder and cables as well as antennas were installed on the models. All tests were performed both in smooth flow as well as turbulent flow.